Incorporating a hole-transport material into the emissive layer of solid-state light-emitting electrochemical cells to improve device performance. Issue 26 (14th July 2015) - Huang, Po-Chin; Krucaite, Gintare; Su, Hai-Ching; Grigalevicius, Saulius
<x xml:space="preserve">Abstract</x> Doping hole transport materials into light-emitting electrochemical cells improves carrier balance and enhances device efficiency.